Factors Influencing the Success Rate of Cardiopulmonary Resuscitation - Aisyah Amanda Hanif; Iwan Abdul Rachman; Hendro Sudjono Yuwono (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Cardiopulmonary resuscitation (CPR) is a series of actions performed on cardiac arrest patients. Not all patients receiving CPR can survive. The outcome of CPR is influenced by several factors. This study was conducted to determine the success rate of CPR and the factors influencing it in Dr. Hasan Sadikin General Hospital in 2013.Methods: This study was conducted by using 168 patient medical records who underwent CPR and met the inclusion criteria in the Resuscitation Room of Dr. Hasan Sadikin General Hospital from January to December 2013. The collected data consisted of age, gender, pre-arrest diagnosis, initial rhythm, response time and clinical outcome of CPR. The results were expressed in frequencies and percentage. The data were analyzed using the chi-square test.Results: The Success rate of CPR was 15.5%. The success rate was higher in patients with cardiac prearrest diagnoses (8.33%, p=0.024). The most common initial rhythm was unshockable rhythms (83.92%), yet patients with shockable heart rhythms had higher success rates (40.74%, p<0.001). All of the surviving patients had response time within the first minute from cardiac arrest.Conclusions: Success rate of CPR in the resuscitation room of Dr. Hasan Sadikin General Hospital during 2013 is still low. The factors influencing the survival rate are the pre-arrest diagnosis and initial heartrhythm. [AMJ.2015;2(4):615–9] DOI: 10.15850/amj.v2n4.657